PEMBENTUKAN, PENGUJIAN AKTIFITAS DAN SELEKTIFITAS BEBERAPA KATALIS PREKURSOR DARI SENYAWA "Ru-KETENILIDINE/SiO2" - Achmad Hanafi Setiawan (Jurnal Kimia Terapan Indonesia, 1997)
The catalyst precursor of Ru3CCO/Si02, RU3C:/SiO2 and RU3:/SiO2 had been identified by "Temperature-Programmed Desorption(TPD)-FTIR-insitu" techniques. The last two precur- sors show a reversible reaction with CO, but the RU3CCO/SiO2 is rather unstable. Test of precursors with C2H4, shows that Ru3CCO/SiO2 produced trans-C4Hg, RU3:/SiO2 produced cis-C4Hg and the RU3C:/SiO2 yielded C3H6, selectively.